Aluminum foil with improved barrier properties
By limiting the number of pores in the manufacturing chain of aluminum alloy foil and adopting a specific annealing cooling process, the problem of high porosity of extremely thin aluminum alloy foils is solved, and better barrier performance and surface characteristics are achieved.
Patent Information
- Application Number
- CN202180085726.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-18
- Filing Date
- 2021-12-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-17
AI Technical Summary
When the existing aluminum alloy foil is at extremely thin layers, the porosity increases, resulting in a degradation of barrier properties. Current standards such as DIN EN 546-4 cannot effectively detect micropores with sizes less than 20 μm.
By taking precautions throughout the manufacturing chain of aluminum alloy foil, limiting the number of pores with a pore size of 1 μm to 200 μm per dm2, with a maximum number of 12, 8 or 6, and reducing microscopic through specific annealing and cooling processes The formation of holes.
The barrier properties of aluminum alloy foil are significantly improved, and are particularly suitable for use as a barrier layer in multi-layer composite materials, ensuring more uniform surface characteristics and adhesion properties.
Smart Images

Figure CN116635548B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum alloy foil having a thickness of at most 12 μm, at most 9 μm or less than 8 μm, wherein the aluminum alloy foil comprises an AA1xxx or A8xxx aluminum alloy in the material state H2x or O. Furthermore, the invention relates to a method for producing the aluminum alloy foil and its use. Background Art
[0002] Aluminium foils of the aforementioned thickness are often used for food packaging, for which they are, for example, part of a multilayer composite material. The aluminium foils contained in the multilayer composite material are used primarily for their good barrier properties. In general, aluminium foils have a very good barrier effect, for example, against water vapour, oxygen, carbon dioxide and larger molecules, such as aromatics. This is achieved by the crystalline structure of the aluminium foil, which essentially prevents the dissolution and diffusion of larger atoms through crystal bonds. Material transport through the aluminium foil can only occur at defects in the aluminium foil, such as pores or holes. Pores are tiny breaks in the aluminium foil, which can be detected by light passing through the foil locally. According to the DIN EN 546-4 standard, pores in aluminium foils are randomly distributed holes with a maximum diameter of 200 μm. According to the definition of DIN EN 546-4, starting from 200 μm, these are roll holes. It is known so far that the porosity of aluminium foils increases with decreasing thickness. Pores can therefore have many different causes. Inclusions or impurities in the metal melt, for example from refractory materials or coarse casting phases (such as Al3Fe), can fall out of the rolled material during the rolling process and leave rolling holes on the aluminum alloy foil. If the particles included in the metal are particularly brittle, such as Al3Fe phases, these particles will also break during the rolling process, and very small fragments will be rolled into the rolled material. This results in the appearance of individual pores or pore lines in the rolled aluminum alloy foil, which impairs the barrier properties of the aluminum alloy foil. In addition, it was found in the research of the present invention that the aluminum alloy foil can also have micropores with a size significantly smaller than 20μm, especially micropores with a size of 1μm to 5μm, which can appear in very large numbers and in the form of locally confined so-called "groups", which usually extend in the rolling direction of the aluminum alloy foil. The pores called micropores can also have an adverse effect on the barrier properties of the aluminum alloy foil.
[0003] In the process of manufacturing aluminum alloy foil for the production of multi-layer composite materials, a necessary process is the final annealing of the rolled aluminum alloy foil for degreasing. When rolling aluminum alloy strips and aluminum alloy foils, rolling oil emulsions and rolling oils are used. Their residues must be removed from the foil after rolling so that the properties of the aluminum alloy foil that are important for processing into multi-layer materials, such as adhesion properties, wetting properties, etc., reach a predetermined level. For this purpose, the aluminum foil is rolled into a coil or a mass-produced roll and annealed as a coil or roll. The rolling medium present on the aluminum alloy foil must be removed from the coil or roll as completely as possible by decomposition and evaporation. The temperature treatment brings the aluminum alloy foil into a partially hard material state H2x or a soft annealed material state O.
[0004] From US patent application US 2002 / 0043310 A1 it is known to degrease AlFe alloy foils with a thickness of less than 12 μm by final annealing at a temperature of 200° C. to 300° C. for at least 50 hours. In material state O with a thickness of less than 12 μm, the porosity of the aluminum alloy foil is less than 10 pores / dm according to DIN EN 546-4. 2 In the examples of the above-mentioned US patent application, a foil with a thickness of 6.6 μm was incompletely annealed at 280° C. for 80 hours. Although the porosity of the known aluminum alloy foil according to the DIN EN 546-4 standard is 6 pores / dm 2 , but this cannot guarantee the barrier properties of aluminum alloy foil.
[0005] DIN EN 546-4 only detects pores with a minimum size of 20 μm or more. Pores with a size of less than 20 μm are not within the scope of DIN EN 546-4. In practice, most pores are round or oval in shape with irregular edges. To determine the pore size, the exact contour of the pore is imaged under a microscope in transmitted light with the edges as sharp as possible, from which the area of the pore is determined and from which the diameter of the circle equivalent to the area is calculated. To measure the porosity in accordance with DIN EN 546-4, rolled aluminum foils are tested using a light box. Here, the aluminum foil sample is placed on the light box, with the matte side facing the tester in the case of double rolled aluminum foil. The test is carried out in a dark room according to DIN EN 546-4 with a maximum remaining brightness of 20 to 50 lux. A light-transmitting glass plate is used as a light box, which is illuminated from below with the help of a light source that provides a uniform illumination intensity of 1000 to 1500 lux. According to a variant of DIN EN 546-4, the porosity is measured by selecting a 1 dm 2The measuring surface with the highest porosity thus represents the worst measuring surface on the foil. According to DIN EN 546-4, the number of pores determined on this measuring surface is determined as a measure of the porosity. However, even if the worst measuring surface of the foil has a very low porosity according to DIN EN 546-4, the barrier properties of the foil cannot always be guaranteed, because the presence of micropores with a detected size of less than 20 μm or a size between 1 μm and 5 μm is not covered by DIN EN 546-4. Summary of the invention
[0006] Starting from this prior art, the object of the present invention is to specify an aluminum alloy foil having improved barrier properties, a method for its production and the use of the aluminum alloy foil according to the invention.
[0007] According to the first teaching of the present invention, the maximum number of holes having a pore size of 1 μm to 200 μm through the aluminum alloy foil is 1 μm per dm 2 12, each dm 2 8 or per dm 2 6, achieving the above objectives.
[0008] It was found that pores not covered by DIN EN 546-4, i.e. pores with a pore size of less than 20 μm, can significantly affect the barrier properties of aluminum alloy foils. By taking into account the smallest pores above 1 μm and limiting the maximum number of pores with a pore size of 1 μm to 200 μm per dm 2 12 or per dm 2 8 or per dm 2 6. The aluminum alloy foil according to the invention can provide significantly better barrier properties than the aluminum alloy foil produced according to DIN EN 546-4. This is because in the aluminum alloy foil according to the invention, the influence of so-called micropores with a size of 1 μm to 20 μm on the barrier properties is also reduced to a minimum. Therefore, the aluminum alloy foil according to the invention is particularly suitable for use as a barrier layer, for example in a multilayer composite material.
[0009] In conventional aluminum alloy foils, pores with a size of 1 to 20 μm, in particular 1 to 5 μm, can be found in so-called “groups” extending in the rolling direction and limited in space. These groups still contain a large number of micropores.
[0010] According to the present invention, each dm 2 The maximum number of pores with a mesopore size of 1 μm to 200 μm is obtained by dividing the aluminum alloy foil into pores with an edge length of 100 mm to 320 mm transverse to the rolling direction of the aluminum alloy foil and a size of 5 to 6 dm. 2The number of pores with a pore size of 1 μm to 200 μm is then determined on each measuring surface, and the number of pores per dm is determined by dividing the number of pores per measuring surface by the selected measuring surface size. 2 The maximum number of pores is measured after final annealing in the material state H2x or O, for example on a coil or a roll of mass production. In this case, mass production means that the aluminum alloy foil has been cut at least in width according to the subsequent application.
[0011] According to the present invention, using each dm 2 The parameter of the maximum number of pores also detects micropores, which have a size of 1 μm to 20 μm and can be locally aggregated and appear in so-called groups. As mentioned above, these groups usually extend in the rolling direction of the aluminum alloy foil and are locally confined to only certain areas of the aluminum alloy foil. However, when determining the number of pores per dm according to the present invention, 2 These micropore groups are reliably detected when the maximum number of pores is 100%, since the entire width of the foil is taken into account. 2 Aluminum alloy foils having a maximum number of pores of 12, 8 or preferably 6 have virtually no micropores and therefore have particularly good barrier properties.
[0012] The number of pores is measured in a completely dark room with a residual brightness of less than 0.25 lux. Here, the surface of the aluminum alloy foil to be measured is placed on a transparent glass surface and fixed with a frame whose internal dimensions correspond to the measurement surface. There is a light source under the glass plate, which can illuminate the measurement surface as evenly as possible. The aluminum foil is fixed by the frame so that the measurement surface on the aluminum alloy foil is defined and there is essentially no residual light from the light source emitted through the aluminum foil. The edges of the aluminum foil must be completely darkened. For example, a flat light source with a brightness of at least 15,000 lux can be used as the light source for the glass plate.
[0013] In a dark room, the measuring surface is photographed with a digital camera centered on the measuring surface, with an exposure time of 30 seconds and an ISO value of 800 or higher, so that the smallest pores with a light penetration size of 1 μm to 20 μm can be detected. The distance of the camera is selected so that the measuring surface is completely detected. However, this distance should be selected as small as possible. The number of pores with a size of 1 μm to 200 μm on the measuring surface of the aluminum alloy foil is then evaluated digitally by image analysis software.
[0014] As mentioned above, this inspection method can also be used to measure micropores with a pore size of 1 μm and above. The results show that, in particular, pores with a pore size of less than 20 μm, especially less than 5 μm, will significantly impair the barrier properties of the aluminum alloy foil. The reason for this is seen in the local, limited, and group appearance of micropores with a high pore density. Therefore, a plurality of micropores will appear in a narrow and limited area of the aluminum alloy foil, and these micropores will greatly reduce the barrier properties of the aluminum alloy foil. However, according to the present invention, each dm 2 Aluminum alloy foils having a pore size of 1 μm to 200 μm and a maximum number of pores of 12, a maximum of 8 or a maximum of 6 have particularly good barrier properties because they do not have any areas with a high micropore density.
[0015] It has been found that in order to provide an aluminum alloy foil according to the present invention, precautions must be taken throughout the manufacturing chain of the aluminum alloy foil to keep the number of voids with a pore size of 1 μm to 200 μm small. Therefore, in the process of manufacturing the aluminum alloy for the aluminum alloy foil, the melt can be filtered before and / or during casting the rolled ingot and passed through a corresponding filter to prevent non-metallic inclusions from entering the alloy. Ideally, the cleaning of the melt should start in the furnace. Therefore, some impurities are removed at an early stage before casting and costs are saved. In the furnace, the melt can be cleaned by flushing with Ar, N2 gas, salt treatment and standing. These measures are often combined for effective melt cleaning. This usually removes carbides, oxides and alkaline metals. Impurities are transported to the surface of the melt with the help of bubbles and absorbed by the slag. After a period of standing, the accumulated impurities are scraped off. During the casting process, cleaning methods, such as degassers and filters, can be used online on the way from the furnace to the cooling mold. The degasser uses a purge gas, such as the purge gas Ar, N2 mentioned above. On the one hand, they have the effect of reducing the hydrogen content in the melt. On the other hand, a filtering / flotation effect is additionally achieved by the purge gas, which can remove particulate inclusions or, for example, scale. The purge gas is usually introduced via a rotor in order to produce fine bubbles, which further increase the degassing and filtering effect. Degassers can be equipped with more than one treatment chamber, so that several degassers connected in series can be used in one system. At the outlet of these degassers with multiple treatment chambers, a chamber for the melt to rest can be provided, in which remaining bubbles and inclusions can migrate to the strip surface and thus be discharged from the melt.
[0016] To further clean the melt, filters with different filtering mechanisms can be used. Foam ceramic filters, such as CFF foam ceramic plate filters and deep bed filters are used as filters. For example, a casting plant with a 70-ton furnace can be equipped with an online degasser of the SIR filter type and a degasser with a throughput of 50 t / h from HYCAST between the furnace and the casting plant, as well as a downstream CFF foam ceramic plate filter with a pore size of finer than 40 ppi ("pores per inch"). Here, the CFF foam ceramic plate filter is used, for example, as a disposable filter and is replaced after each casting. Alternatively, a deep bed filter, also known as a bulk bed filter (Schüttbettfilter), can also be used. Here, the filter medium is alternately filled with balls and ball fragments, which are made of, for example, flaky aluminum oxide with a diameter of up to 20 mm, and are layered in a filter box of approximately 2x 3m.
[0017] In the case of DC casting, the cast rolled ingot is homogenized at a temperature and duration set for the specific alloy type, while also reducing coarse casting phases in the cast rolled ingot, such as coarse Al3Fe casting phases, thereby avoiding the corresponding brittle particles in very thin rolled aluminum alloy foils.
[0018] In the strip casting process (CC casting), for example using a twin roll caster (TRC), the molten metal is fed, for example, to water-cooled rolls, where it solidifies. The solidified strip is then immediately rolled further. The melt undergoes the same cleaning steps in the furnace as in DC casting. This removes foreign phases such as carbides and oxides. Unlike DC casting, the strip produced in CC casting tends to form so-called center segregation, which is present in the form of coarse intermetallic phases, such as AlFe phases in AlFeSi alloys; or in the form of enrichment of other alloying elements. The composition of the precipitates depends on the respective alloy composition and the selected casting process parameters. For example, the composition of the AlFeSi alloy influences the width of the temperature interval in which the melt solidifies, which is also called the solidification interval. The wider the solidification interval, the greater the tendency to form center segregation. In order to suppress the formation of segregation, for example, the casting speed is reduced while increasing the cooling power. For example, the casting speed in the TRC process is between 1000 and 2500 mm / min. The cooling power is affected by the outer diameter of the rolls. The larger the outer diameter, the higher the cooling power. For example, for AA8xxx alloys with a solidification range of 30K, a casting speed of 1000 to a maximum of 1500 mm / min can be selected at a roller diameter of about 600 mm. On the contrary, for purer aluminum alloys, such as AA1050 or AA1070 types, a higher casting speed of 2000 to 2500 mm / min at a roller diameter of about 900 mm is advantageous to compensate for center segregation.
[0019] After the aluminum foil is rolled, degreasing is carried out by an annealing process to provide a material state of H2x and O. It is recognized here that the degreasing process by annealing the rolled aluminum alloy foil can have a great influence on the presence of pores with a pore size of 1 μm to 20 μm. Surprisingly, the formation of micropores can be greatly reduced by reducing the annealing temperature to a maximum of 245°C, while extending the annealing time and taking into account a special cooling stage of up to 3 hours at 100°C.
[0020] According to a further design of the present invention, the aluminum alloy foil according to the present invention is characterized in that the aluminum alloy foil has an oxide layer thickness of 3 to 6 nm measured along the entire width of the aluminum alloy foil, wherein the oxide layer thickness of the aluminum alloy foil on the edge region of the aluminum alloy foil is at most 30% greater than that of the middle region of the aluminum alloy foil. Not only is the oxide layer thickness particularly thin, 3 to 6 nm, but it is also uniform over the width of the aluminum alloy foil, with only a slight increase toward the edge region. The reason for this advantageous property of the aluminum alloy foil according to the present invention is the specific degreasing annealing and subsequent cooling process. This results in more uniform surface properties for use in multilayer composite materials. For example, the adhesion properties of the aluminum foil are particularly stable over the entire width due to the uniform oxide layer thickness distribution. The thickness of the aluminum oxide layer can be measured by methods such as ATR (attenuated total reflection) infrared spectroscopy. By this measurement method, the thickness of the oxide layer can be detected over the entire thickness with a resolution in the sub-nanometer range.
[0021] According to a further embodiment of the aluminum alloy foil, the thickness of the oxide layer is a maximum of 5 nm on both the matte and the shiny side of the aluminum alloy foil. Due to the reduction in the thickness of the oxide layer during the production process, the surface of the aluminum alloy foil has better adhesion properties, which makes the aluminum alloy foil very suitable for multilayer composite materials, for example for packaging materials, for example as part of flat bag packaging.
[0022] If according to the next design, the aluminum alloy foil has an aluminum alloy, the alloy composition thereof is calculated by weight % as follows:
[0023] 0.05%≤Si≤0.30%,
[0024] 0.7≤Fe≤1.3%,
[0025] Cu≤0.05%,
[0026] Mn≤0.05%,
[0027] Mg≤0.05%,
[0028] Cr≤0.05%,
[0029] Zn≤0.10%,
[0030] Ti≤0.025%,
[0031] The remainder is Al and inevitable impurities of up to 0.05 wt % individually and up to 0.15 wt % in total, thereby providing an aluminum alloy foil having high strength and low cost.
[0032] Despite the low content of alloying components, the properties of AlFeSi alloys are decisively influenced by the elements in the solution and the binary AlFe phase and the ternary AlFeSi phase. When the casting solidifies, Al mixed crystals supersaturated with Si and Fe are formed. Due to the low solubility, Fe precipitates in the form of the intermetallic compound Al3Fe and is deposited at the grain boundaries of the Al mixed crystals. This binary phase is stable and hardly changes during subsequent thermomechanical treatments. Only during rolling is the AlFe phase crushed under the action of the rolling force. The equilibrium solubility of Fe in aluminum is very low, with a maximum of 400 ppm (655°C). The maximum solubility of Si is much higher, at 1.65 wt% (577°C). Strength and elongation are positively affected by the amount of Si added. Silicon forms AlFeSi dispersions and therefore contributes to the increase in strength due to particle hardening, as well as to the increase in elongation. Si atoms present in the Al matrix in dissolved form contribute to mixed crystal hardening. Silicon-containing AlFeSi precipitates are also nucleation centers for recrystallization and thus improve the recrystallization properties of the aluminum alloy foil. However, as the Si content increases, the solubility of iron decreases, thereby also reducing the strength contribution of Fe through mixed crystal hardening, so the Si content is preferably limited to a maximum of 0.30 wt. %. In order to prevent a decrease in strength, the Si content is preferably at least 0.05 wt. %.
[0033] Iron in solution also leads to an increase in strength, while fine grains and thermal stability of the aluminum alloy foil also increase, so it is preferred to contain at least 0.7% by weight of iron. If the Fe content is less than 0.7% by weight, the proportion of iron in the solution will be reduced, and a low phase density will occur, thereby reducing the strength of the aluminum alloy foil. However, the solubility of iron in the aluminum matrix is quite low, and AlFe intermetallic phases are formed when the casting solidifies. These precipitates are coarse and are quite detrimental to mechanical properties. Therefore, the iron content is limited to 1.3% by weight.
[0034] Due to the high solubility of Cu, Mn, Mg or Cr in the aluminum matrix, these elements remain essentially in solution at the upper limit of the maximum 0.05 weight % given and contribute to the strength of the aluminum alloy foil. Excessively high weight proportions of copper, manganese, magnesium or chromium can be used to further increase the strength. However, they can also lead to an undesirable increase in the rolling force necessary during the rolling of the aluminum foil. Zinc can also increase the strength, but also has a positive effect on the refinement of the grain structure, so a maximum weight proportion of 0.10% is preferably permitted.
[0035] Titanium acts as a grain refiner, resulting in a slight increase in strength and recrystallization temperature. Aluminum alloy foil contains up to 0.025 wt. % titanium to adjust the aluminum alloy foil to have good casting properties and a fine grain structure with good recrystallization.
[0036] According to a preferred variant, the aluminum alloy of the aluminum alloy foil has at least one of the following limitations of alloying components in % by weight:
[0037] 0.8%≤Fe≤1.15%,
[0038] Cu≤0.05%,
[0039] 0.01%≤Mn≤0.04%, preferably 0.015%≤Mn≤0.035%, particularly preferably 0.018%
[0040] ≤Mn≤0.025%,
[0041] Mg≤0.01%, preferably Mg≤0.005%, particularly preferably Mg≤0.0035%,
[0042] Cr≤0.02%,
[0043] Zn≤0.07% and / or
[0044] 0.005%≤Ti≤0.025%.
[0045] As described in the previous section, the weight ratio of Si to Fe is chosen so that in a manufacturing process matched to the requirements of the foil product, an optimal Fe solution state is obtained at an optimal AlFe, AlFeSi phase density, and thus the best strength characteristic values can be obtained. Starting from the preferred iron content of 0.8 wt. %, the strength and thermal stability of the aluminum alloy foil are increased again. The coarsening of the grain structure is also offset. Exceeding 1.15 wt. % iron leads to an increase in the density of the intermetallic aluminum-iron casting phase, which leads to a decrease in elongation and a deterioration of the porosity.
[0046] The manganese content of the aluminum alloy in weight percent is preferably 0.01% ≤ Mn ≤ 0.04%, preferably 0.015% ≤ Mn ≤ 0.035%, and particularly preferably 0.018% ≤ Mn ≤ 0.025%. When the Mn content is less than 0.01% by weight, the strength and thermal stability of the aluminum alloy foil will decrease. Conversely, when the manganese content exceeds 400 ppm, the rolling force during the rolling of the aluminum foil will increase, thereby also increasing the processing cost. Therefore, a good compromise is achieved between increased strength and processing costs at a content of 0.0150% by weight to 0.035% by weight, preferably at a content of 0.018% by weight to 0.025% by weight.
[0047] The element Mg is characterized by good diffusion in the aluminum matrix and therefore tends to be enriched on the surface of the aluminum foil. Therefore, the content of magnesium is limited to a maximum of 0.01% by weight, preferably a maximum of 0.005% by weight, and particularly preferably a maximum of 0.0035% by weight. Maintaining these values ensures that at the temperatures used in the customer's process, no undesirable magnesium oxide or magnesium hydroxide products are formed due to the enrichment of magnesium on the surface of the aluminum foil, which would have a negative impact on the adhesion of the coating.
[0048] The Zn content is preferably limited to a maximum of 0.07 wt % in order to reduce the rolling force during rolling of the aluminum foil.
[0049] Cr and Ti are present in aluminum alloys only in low contents. The chromium content is limited to a maximum of 0.02% by weight. Cr dissolves well in the aluminum matrix and even at low contents leads to a significant increase in rolling forces during aluminum foil rolling. The maximum weight proportion of titanium is limited to 250 ppm, wherein a minimum Ti content of at least 50 ppm leads to better castability while having good mechanical properties. This ensures, on the one hand, that additional costs due to unnecessary additions of alloying elements are avoided, and on the other hand, that the aluminum foil flow stress and rolling forces do not exceed the limits specified in the aluminum foil rolling process.
[0050] According to a further design of the aluminum alloy foil of the present invention, the yield strength Rp0.2 measured in the transverse, longitudinal or diagonal direction of the rolling direction in the material state O is at least 55 MPa, preferably at least 58 MPa. 2 Due to the reduced maximum number of pores, the aluminum alloy foil according to the invention is very suitable for processing into multilayer composite materials.
[0051] The aluminum alloy foil according to the invention also has an improvement in the C-coating of the aluminum alloy foil, i.e. the amount of carbon from the rolling medium that remains on the aluminum alloy foil after annealing. According to a further design of the aluminum alloy foil, the C-coating in the middle of the aluminum alloy foil is 20% lower than in the edge region of the aluminum alloy foil. Typically, the difference between the edge and the middle region of the aluminum alloy foil over the entire strip width is significantly greater. Also due to the more uniform C-coating over the width of the aluminum alloy foil, the aluminum alloy foil according to the invention has more uniform properties, such as adhesion properties.
[0052] To determine the C coating of aluminum alloy foils, 5 cm wide strips of aluminum foil in the gram range are cut longitudinally from annealed aluminum foil coils or annealed aluminum foil rolls, wound up, accurately weighed and burned in a quartz tube at 600 ° C in an oxygen stream. The carbon dioxide produced by rolling oil and its residues is quantitatively measured by coulometric method or infrared spectroscopy. The sample area is calculated from the weight, density and thickness of the aluminum foil. The C coating is expressed in mg / m 2Aluminum foil is given. Samples are taken at least in the middle and at the edge of the annealed aluminum alloy foil. For example, a total of 5, 7, 9 or more strips can be extracted symmetrically relative to the middle of the annealed aluminum alloy foil, taking into account the edge, to determine the distribution of the C coating on the width of the aluminum alloy foil.
[0053] According to a further design of the aluminum alloy foil of the present invention, the aluminum alloy foil has a tensile strength of at least 80 MPa measured transversely, longitudinally and / or diagonally in the rolling direction in material state H2x or O. In order to achieve a lower maximum number of pores, the aluminum alloy foil with the above composition is subjected to the specific manufacturing steps described, which will increase the tensile strength Rm to more than 80 MPa in material state H2x, especially in material state O. The higher tensile strength allows the web tension to be increased during the processing of the aluminum alloy foil, thereby speeding up the processing of the aluminum alloy foil, for example, when manufacturing a multilayer composite material.
[0054] This also applies to the next embodiment of the aluminum alloy foil according to the present invention, according to which the elongation at break A of the aluminum alloy foil is 100mm At least 6.2%, preferably at least 6.5%, measured diagonally in the rolling direction. Surprisingly, despite the increased values of tensile strength and yield strength, the values of elongation at break diagonally in the rolling direction remain almost unchanged and only slightly decrease compared to standard aluminum foil. Improved elongation at break values A 100mm The processing of aluminum alloy foils is also advantageous, especially in the production of aluminum composite materials with multilayer systems and in the production of packaging, especially in deep drawing, bending, folding and sealing, because the risk of tearing of the aluminum alloy foil during processing is reduced.
[0055] According to a second teaching of the present invention, the above object is achieved by a method for producing an aluminum alloy foil, the method comprising the following steps:
[0056] - producing an aluminium alloy strip for cold rolling by casting a rolled ingot from an AA1xxx or AA8xxx aluminium alloy, wherein the aluminium alloy melt is filtered before and / or during casting the rolled ingot, the cast rolled ingot is homogenised and the rolled ingot is hot rolled into a hot strip or a cast strip is continuously cast from a filtered AA8xxx or AA1xxx type aluminium alloy melt and the cast strip is subsequently selectively hot rolled,
[0057] - cold rolling the aluminium alloy strip to a first intermediate thickness,
[0058] - subjecting the cold-rolled aluminium alloy strip to recrystallisation annealing at this intermediate thickness,
[0059] - cold rolling the aluminium alloy strip to a second intermediate thickness,
[0060] - doubling the aluminum alloy strip and performing intermediate annealing,
[0061] - rolling the doubled aluminum alloy strip to the final thickness of the doubled foil,
[0062] - separating and winding up the individual layers, each with a final thickness of at most 12 μm, at most 9 μm or less than 8 μm, wherein the aluminum alloy foil is selectively produced in batches in a plurality of rolls, and
[0063] - Final annealing of the coil or batch-produced coils for at least 150 h at an oven air temperature of 200-245 ° C, preferably up to 240 ° C or up to 235 ° C, and finally a final cooling phase of at least 3 h at an oven air temperature of 100 ° C.
[0064] It has been found that, starting from a filtered aluminum alloy cast-rolled ingot or cast-rolled strip composed of an AA1xxx or A8xxx aluminum alloy, until a degreasing annealing is carried out in the form of a final annealing at a furnace air temperature of 200 to 245° C. for at least 150 h and a final cooling phase at a furnace air temperature of 100° C. for at least 7 h, particularly advantageous properties of an aluminum alloy foil in the H2x or O material state can be achieved by combining the above-mentioned method features. In addition to the advantageous properties related to the oxide layer thickness of the aluminum alloy foil and its carbon C coating, firstly the pores per dm2 of the aluminum alloy foil with a diameter of 1 μm to 200 μm can be significantly reduced. 2 The maximum number of pores per dm2 is thus reduced, thereby stabilizing the barrier properties of the produced aluminum alloy foil in a process-reliable manner. It has been found that significantly fewer or no pores with a size of less than 5 μm can be found in the aluminum alloy foil when the required temperature window is observed during the annealing process and the cooling phase. Lower temperatures, for example up to 240°C or up to 235°C, show lower pores per dm2. 2 The maximum number of pores. The cooling phase at 100°C of at least 3 hours, preferably 7 hours, causes a "gentle" cooling of the aluminum foil roll in the furnace, so that all layers in the aluminum foil roll reach a temperature of about 100°C. The effect of the long holding time of at least 3 hours, preferably at least 7 hours, is that the temperature gradient in the roll is as small as possible before the roll leaves the furnace. This prevents the aluminum foil layers from warping during the final cooling in air. In addition, after annealing at 200°C to a maximum of 245°C, the surface of the aluminum foil is chemically activated. By controlling the cooling to 100°C, strong oxidation of the aluminum foil surface with humid air can be prevented, thereby preventing the formation of undesirable oxidation products on the aluminum foil surface, which can, for example, cause adhesion of the aluminum foil roll layers. As a result, improved unwinding properties of the aluminum alloy foil can be guaranteed.
[0065] For strip casting, the casting speed is adapted to the solidification range. For example, when a twin-roll casting process is used, the casting speed varies between 1000 and 2500 mm / min. The cooling power is affected by the outer diameter of the roller, so a larger outer diameter can provide a higher cooling power. For example, for AA8xxx alloys with a solidification range of 30K, a casting speed of 1000 to a maximum of 1500 mm / min can be selected when the roller diameter is about 600 mm. On the contrary, for purer AA1050 or AA1070 alloys, a higher casting speed of 2000 to 2500 mm / min can be selected when the roller diameter is, for example, 900 mm. As a result, the formation of center segregation can be avoided. At the same time, this also greatly reduces the formation of pores in the aluminum alloy foil.
[0066] If, according to a further embodiment of the method according to the invention, the aluminum alloy has the following alloy composition in % by weight:
[0067] 0.05%≤Si≤0.30%,
[0068] 0.7%≤Fe≤1.3%,
[0069] Cu≤0.05%,
[0070] Mn≤0.05%,
[0071] Mg≤0.05%,
[0072] Cr≤0.05%,
[0073] Zn:≤0.10%,
[0074] Ti: ≤0.025%,
[0075] The remainder is Al and unavoidable impurities of up to 0.05 wt. % individually and up to 0.15 wt. % in total, and
[0076] - recrystallization annealing of the cold rolled strip is carried out at a furnace air temperature of 450°C to 550°C for at least 5 h, and
[0077] - Intermediate annealing after doubling of the strip at a furnace air temperature of 240°C to 320°C for 0.5 h can produce an aluminum alloy foil with a thickness of, for example, 6.3 μm, whose yield strength value Rp0.2 measured transversely, longitudinally or diagonally to the rolling direction in material state O is at least 55 MPa, preferably at least 58 MPa. The increased yield strength value improves the handling of the partially annealed aluminum alloy foil in further aluminum alloy foil processing, for example processing into multilayer composite materials. For the influence of the individual alloy components, please refer to the explanation of aluminum alloy foil.
[0078] According to a further design of the method, the aluminum alloy has at least one of the following limitations on the alloy composition in wt %:
[0079] 0.8%≤Fe≤1.15%,
[0080] Cu≤0.05%,
[0081] 0.01%≤Mn≤0.04%, preferably 0.015%≤Mn≤0.035%, particularly preferably 0.018%≤Mn≤0.025%,
[0082] Mg≤0.01%, preferably Mg≤0.005%, particularly preferably Mg≤0.0035%, Cr≤0.02%,
[0083] Zn≤0.07% and / or 0.005%≤Ti≤0.025%.
[0084] Regarding the technical effect of the preferred limitation of the aluminum alloy composition, please refer to the explanation of the aluminum alloy foil according to the present invention. In the method of manufacturing the aluminum alloy foil, the focus is not only on the mechanical properties, but also on the rolling force and the rolling force per dm 2 The lowest possible maximum number of pores.
[0085] All specified mechanical parameters, such as tensile strength R m , yield strength R p0.2 Or elongation at break A 100mm , are measured in accordance with DIN EN 546-2. The elongation at break value refers only to A 100mm The numerical value of .
[0086] In addition to casting the filtered aluminum alloy foil alloy, according to a further design, it is advantageous to homogenize the rolled ingot at 420°C to 600°C for at least 7 hours. During the homogenization process, the already cooled cast ingot is placed at a temperature close to the melting point to reduce or eliminate the microsegregation that occurs during the solidification of the ingot. During the homogenization process, the unstable phase is also dissolved and converted into a stable phase. After preheating before homogenization, when the ingot is cooled again, the fine phase in the form of a dispersion precipitates. Therefore, the homogenization achieves the setting of a homogeneous structure with the lowest possible proportion of microsegregation, and also achieves a precipitate structure that is favorable to the rollability and the properties of the final product.
[0087] It has also been found that, according to a further design, it is advantageous to hot-roll the rolled ingot to a hot-rolled final thickness of 2 mm to 4 mm during the hot rolling process and to have a hot-rolled final temperature of between 300° C. and 350° C. after the hot-rolled strip is coiled. This allows static recrystallization of the hot-rolled strip after coiling, thereby achieving a maximum rolling rate in the first cold rolling. This in turn has a positive effect on the recrystallization during the first intermediate annealing, since the energy for recrystallization is reduced due to the high strengthening achieved by cold rolling with a high rolling rate.
[0088] According to a further embodiment of the method, additional positive properties can be achieved by carrying out a final annealing at a temperature of 200° C. to 225° C. for at least 150 hours. In particular, by reducing the upper temperature to 225° C., micropores smaller than 20 μm, in particular micropores with a size of 1
[0089] The occurrence of micropores in the range of μm to 5 μm is even more restricted, so that the barrier properties of aluminum alloy foils for multilayer composites, for example in the field of composite packaging, are guaranteed by the production process.
[0090] Finally, the use of the aluminum alloy foil according to the invention or the aluminum alloy foil produced by the method according to the invention for multilayer composite materials, in particular for the packaging sector, is particularly advantageous. Furthermore, the corresponding aluminum alloy foil can also be advantageously used in packaging that has to be folded, bent, slotted, deep-drawn or stretched, because here the very good barrier properties of the aluminum alloy foil ensure better protection for the products packaged therewith.
[0091] Cardboard packages, in particular sterilizable cardboard packages of a multilayer composite material with an aluminum layer, can benefit from the very good barrier properties of the aluminum alloy foil according to the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0092] The present invention will be described in more detail below with the help of embodiments in conjunction with the accompanying drawings, in which:
[0093] Figure 1a A scanning electron microscope image of the rolled porosity of a foil is shown, which was taken according to the DIN EN 546-4 standard,
[0094] Figure 1b Scanning electron microscope image of a milled sheet showing a stack of aluminum alloy foil with micropores,
[0095] Figure 2 The measurement is shown for each dm across the foil width. 2 Schematic cross-sectional view of a device with a maximum number of pores,
[0096] Figure 3 shows the method for determining each dm 2Schematic top view of the measurement surface with the maximum number of pores, and
[0097] Figure 4a ), b), c) show digital photographs of aluminum foil samples according to the invention and not according to the invention. DETAILED DESCRIPTION
[0098] Figure 1a First, a scanning electron microscope image of an aluminum alloy foil with a thickness of 6 μm in material state O is shown, which has rolling pores with a diameter of about 30 μm. The currently known DIN EN 546-4 tests the corresponding pores in aluminum alloy foils, because according to this standard, pores with a size of more than 20 μm up to 200 μm must be taken into account.
[0099] on the other hand, Figure 1b Scanning electron microscope images of a polished sheet of a foil stack with micropores, prepared using a cross-section polisher (CSP). The foil in the middle shows an indentation of approximately 1 μm and a micropore channel. Assuming that the micropores are three-dimensional structures, they form connections from one side of the foil to the other that are not always straight.
[0100] It is easy to imagine that a large number of micropores with a size significantly smaller than 20 μm, for example 1 to 5 μm, would also lead to a negative impact on the barrier effect of the aluminum alloy foil.
[0101] 546-6 standard, per dm 2 Aluminum alloy foils with a low number of pores do not necessarily have a good barrier effect. This applies to all aluminum alloy types mentioned here, as well as to alloys of the AA1xxx or AA8xxx types.
[0102] In contrast, the aluminum alloy foil according to the invention made of the above-mentioned AA8xxx and AA1xxx aluminum alloy types with a thickness of at most 12 μm, at most 9 μm or less than 8 μm has a pore size of 1 μm to 200 μm per dm 2 The number of pores is a maximum of 12, a maximum of 8 or a maximum of 6, so that pores of a size of 1 μm to 20 μm which are not taken into account according to DIN EN 546-6 are also taken into account. By virtue of the aluminum alloy foil according to the invention having a pore size of 1 μm to 200 μm, so that also very small pores starting from a pore size of 1 μm are included, which have a particularly low maximum number of pores, better barrier properties of the aluminum alloy foil can be provided.
[0103] Figure 2 The measurement is shown for each dm across the foil width. 2 Schematic cross-section of the device with maximum pore number. Figure 2An aluminum alloy foil 1, a light source 2, such as an overhead projector, and a camera 3 are shown for filming a measurement surface 3A for evaluation. The device must be placed in a dark room so that no scattered light can influence the measurement. In a dark room, the residual brightness is preferably less than 0.25 lux. The aluminum alloy foil 1 is fixed in the measurement range by a frame 5, which completely surrounds the measurement surface, so that the aluminum alloy foil 1 is positioned as flat as possible in the measurement surface 3A.
[0104] The light source 2 illuminates the aluminum alloy foil 1 through the transparent glass plate. Figure 2 2. However, it can be seen from the range of the light source 2 that the illumination of the aluminum alloy foil 1 from below should be as uniform as possible. The distance of the camera 3 must be selected depending on the size of the measurement surface to be photographed and the lens used. A lens with the smallest possible focal length should be selected so that the smallest distance can be selected in order to photocopy the measurement surface with the best possible resolution.
[0105] The light source 2 is completely darkened by the aluminum alloy foil and the frame 5, so that only the light that penetrates the aluminum alloy foil 1 through the pores in the measuring surface 3A can reach the camera. The aluminum alloy foil 1 is divided into preferably at least three or at least five measuring surfaces along the entire width 4, so that the entire width of the foil is measured. Since after the aluminum foil is rolled, the aluminum alloy foil is usually mass-produced into rolls with a certain width and then annealed, the width 4 of the aluminum alloy foil 1 refers to the width of the aluminum foil roll or, in the absence of mass production, the entire width of the aluminum foil coil. By dividing into different measuring surfaces 3A, preferably into at least five measuring surfaces 3A along the entire width of the aluminum alloy foil, it is also possible to detect a group of pores with a size of 1 μm to 20 μm that occur locally. According to the DIN EN 546-4 standard, these pores are not taken into account in the known porosity measurement.
[0106] The following test device was used for measuring the aluminum foil: The light source was an overhead projector from Andreas+Kern with an optical halogen lamp of 36V and 400W and a luminous flux of up to 6000 lumens. The aluminum foil to be inspected was placed on the projector and fixed by a metal frame of determined dimensions so that the aluminum foil lay flat on the projector and was sealed on the sides. The camera used was a Sony Alpha 6000 with a pixel of 6000×4000 and a lens type of Minolta MD Rokkor 50mm f1.4. An aperture value of 2, an ISO value of 800 and an exposure time of 30 seconds were used for photography. The distance from the camera sensor to the aluminum foil was 700 mm. The image analysis used the Image Analyzer software. As shown in FIG4 , the measuring surfaces 3A were arranged adjacent to each other without gaps in the width 4 perpendicular to the longitudinal direction 7 of the aluminum alloy foil 1, so that the entire width of the aluminum alloy foil 1 was measured. The dimensions of the measuring surface were 183 mm×276 mm, thus 5.0508 dm2 The software then determines the number of pores in the range of 1 μm to 200 μm from the measurement surface with the most pores and calculates the value by dividing the number of pores measured on the worst measurement surface by the dm 2 The total area of the unit is normalized to 1dm 2 The result is rounded to an integer. By this measuring method, in particular the smallest pores with a size of less than 20 μm, especially pores of 5 μm to 1 μm, which occur locally, can be detected and counted.
[0107] As Example A, an aluminum alloy having an alloy composition in accordance with Table 1 is cast into a rolled ingot. The aluminum alloy melt is treated with a purge gas before and / or during casting of the rolled ingot and filtered through a degasser and a deep bed filter. As mentioned above, the function of this filtering is to prevent non-metallic impurities from entering the subsequent rolled ingot from the melt. The rolled ingot is then homogenized, which for the present aluminum alloy is carried out in a temperature range of 420-600° C. for at least 5 hours in order to return as much of the casting phase as possible to the solution.
[0108] The rolled ingot is then hot rolled in a hot rolling process to a hot rolling final thickness of 2 mm to 4 mm and coiled as a hot strip at a hot rolling final temperature of 300° C. to 350° C. The hot strip is cold rolled in a number of cold rolling passes to an intermediate thickness of, for example, 0.60 mm to a maximum of 0.80 mm. A recrystallization annealing is then carried out at a furnace air temperature of 450° C. to 550° C. for at least 5 hours. The aluminum strip thus recrystallized undergoes a further cold rolling step to a second intermediate thickness of between 11 μm and 20 μm and is doubled for foil rolling. After doubling, an intermediate annealing is carried out at a furnace air temperature of 240° C. to 320° C. for half an hour. The doubled strip is then foil rolled.
[0109] After separation of the aluminum foil layer, the coil is selectively mass-produced into rolls. The final thickness of the aluminum alloy foil is a maximum of 12 μm, a maximum of 9 μm or less than 8 μm. In this embodiment, the thickness of the aluminum alloy foil reaches 6.3 μm. After the selective mass production, i.e. after the aluminum foil is cut into roll widths and rolled up, the roll is finally treated at a furnace air temperature of 200°C to 245°C for at least 150 hours, and the cooling stage at a furnace air temperature of 100°C is at least 3 hours. Unlike Example A according to the invention, Comparative Example B is annealed at a temperature of 330°C for 50 hours and then cooled to room temperature.
[0110] Table 2 first shows the mechanical characteristics of aluminum alloy foils of two variants A and B according to DIN EN 546-2. It has been shown that, surprisingly, the aluminum alloy A according to the invention has a higher yield strength R p0.2 And tensile strength value Rm , but like variant B annealed at high temperature, the elongation at break value A measured diagonally in the rolling direction 100mm On the other hand, the comparative variant B shows a significantly lower yield limit value R p0.2 and lower tensile strength value R m .
[0111] Measurements of the oxide layer thickness distribution over the width of the aluminum alloy foil also show that variant A according to the invention has a more uniform oxide layer thickness distribution over the roll width than variant B not according to the invention.
[0112] Now, according to the invention, the manufacturing variants A and B are compared with respect to each dm 2 The maximum number of pores was determined. Meanwhile, aluminum alloy foils were further produced from Alloy 1 and subjected to final annealing using different methods. Figure 2 Measurements made with the apparatus described in the invention show that the furnace air temperature is up to 245°C for 150 hours and then cooled for 7 hours at a furnace air temperature of 100°C. 2 As the maximum number of pores per dm 2 10 pcs.
[0113] Starting from a temperature of 260° C. for 100 h or 280° C. for 100 h, and especially at a furnace air temperature of 330° C. for 50 h without a cooling phase, the values of the maximum number of pores with a size of 1 μm to 200 μm increase significantly. Figure 4a This is also illustrated by the photograph of an aluminum alloy foil not according to the invention annealed according to variant B shown in FIG. Figure 4b Compared to the variants annealed according to the invention of 4c) and 4d), very numerous, very small pores with a size of less than 20 μm can be seen. Figure 4b The aluminum alloy foils in ) and c) were annealed at 245°C or 220°C in the furnace air temperature for 150 h and at 100
[0114] Cool at a furnace temperature of ℃ for 7 hours. Figure 4b ) and 4c), the aluminum alloy foil according to the present invention shows no microporous population, and thus the barrier properties are significantly improved.
[0115] Table 1 Alloy composition by weight, the rest is Al,
[0116]
[0117] Table 2 Mechanical parameters in accordance with DIN EN 546-2, state O
[0118]
[0119] Table 3 Oxide layer thickness in [nm], state O
[0120]
[0121] Table 4: Maximum number of pores
[0122]
Claims
1. Aluminum alloy foil with a thickness of at most 12 μm, wherein the aluminum alloy foil comprises an AA1xxx or AA8xxx aluminum alloy in the material state H2x or O, It is characterized in that The aluminum alloy foil comprises an aluminum alloy, and the alloy composition of the aluminum alloy is calculated as follows by weight %: 0.05%≤Si≤0.30%, 0.7≤Fe≤1.3%, Cu≤0.05%, 0.01%≤Mn≤0.025%, Mg≤0.05%, Cr≤0.05%, Zn≤0.10%, Ti≤0.025%, The remainder is Al and unavoidable impurities of up to 0.05 wt. % individually and up to 0.15 wt. % in total, The maximum number of pores having a pore size of 1 μm to 200 μm per dm 2 12 pieces.
2. The aluminum alloy foil according to claim 1, characterized in that The thickness of the aluminum alloy foil is at most 9 μm.
3. The aluminum alloy foil according to claim 1, characterized in that The thickness of the aluminum alloy foil is less than 8 μm.
4. The aluminum alloy foil according to claim 1, characterized in that The maximum number of pores having a pore size of 1 μm to 200 μm per dm 2 8.
5. The aluminum alloy foil according to claim 1, characterized in that The maximum number of pores having a pore size of 1 μm to 200 μm per dm 2 6 pieces.
6. The aluminum alloy foil according to claim 1, It is characterized in that The aluminum alloy foil has an oxide layer thickness of 3 to 6 nm measured along the entire width of the aluminum alloy foil, wherein the oxide layer thickness on the edge region of the aluminum alloy foil is at most 30% greater than that in the middle region of the aluminum alloy foil.
7. The aluminum alloy foil according to claim 6, It is characterized in that The thickness of the oxide layer on both the matte and shiny sides of the aluminum alloy foil is a maximum of 5 nm.
8. The aluminum alloy foil according to claim 1, It is characterized in that The aluminum alloy of the aluminum alloy foil has at least one of the following alloy composition restrictions calculated in weight %: 0.05%≤Si≤0.30%, 0.8%≤Fe≤1.15%, Cu≤0.05%, 0.018%≤Mn≤0.025%, Mg≤0.01%, Cr≤0.02%, Zn≤0.07% and / or 0.005%≤Ti≤0.025%.
9. The aluminum alloy foil according to claim 8, characterized in that The Mg content in the aluminum alloy of the aluminum alloy foil is ≤ 0.005%.
10. The aluminum alloy foil according to claim 8, characterized in that The Mg content in the aluminum alloy of the aluminum alloy foil is ≤ 0.0035%.
11. The aluminum alloy foil according to claim 1 or 8, It is characterized in that The aluminum alloy foil has a yield strength Rp0.2 of at least 55 MPa in material state O, measured transversely, longitudinally or diagonally to the rolling direction according to DIN EN 546-2.
12. The aluminum alloy foil according to claim 11, characterized in that The aluminum alloy foil has a yield strength Rp0.2 of at least 58 MPa in material state O, measured transversely, longitudinally or diagonally to the rolling direction according to DIN EN 546-2.
13. The aluminum alloy foil according to claim 1, It is characterized in that The aluminium alloy foil has a tensile strength Rm of at least 80 MPa in the material state H2x or O according to DIN EN 546-2, measured transversely, longitudinally and / or diagonally to the rolling direction.
14. The aluminum alloy foil according to claim 7 or 8, It is characterized in that Elongation at break of aluminum alloy foil A 100mm , measured diagonally in the rolling direction, at least 6.2 % in accordance with DIN EN 546-2.
15. The aluminum alloy foil according to claim 14, characterized in that Elongation at break of aluminum alloy foil A 100mm , measured diagonally in the rolling direction, at least 6.5 % in accordance with DIN EN 546-2.
16. A method for producing an aluminum alloy foil according to any one of claims 1 to 15, wherein the method comprises the following steps: - producing an aluminium alloy strip for cold rolling by casting a rolled ingot from an AA1xxx or AA8xxx aluminium alloy, wherein the aluminium alloy melt is filtered before and / or during casting of the rolled ingot, the cast rolled ingot is homogenised, and the rolled ingot is hot rolled into a hot strip, or Continuously casting a cast strip from a filtered AA8xxx or AA1xxx aluminum alloy melt and subsequently selectively hot rolling the cast strip, - cold rolling the aluminium alloy strip to a first intermediate thickness, - subjecting the cold-rolled aluminium alloy strip to recrystallisation annealing at this intermediate thickness, - cold rolling the aluminium alloy strip to a second intermediate thickness, - Doubling of aluminum alloy strips and intermediate annealing, - rolling the doubled aluminum alloy strip to the final thickness of the doubled foil, - separation and winding of individual layers, each with a final thickness of at most 12 μm, wherein the aluminum alloy foil is produced in batches in a plurality of rolls, and - Final annealing of the coil or batch-produced coils for at least 150 h at a furnace air temperature of 200 to 245 ° C, followed by a cooling phase of at least 3 h at a furnace air temperature of 100 ° C.
17. The method according to claim 16, characterized in that A final cooling phase is carried out at an oven air temperature of 100° C. for at least 7 h.
18. The method according to claim 16, It is characterized in that The aluminum alloy has the following alloy composition in weight %: 0.05%≤Si≤0.30%, 0.7%≤Fe≤1.3%, Cu≤0.05%, 0.01%≤Mn≤0.025%, Mg≤0.05%, Cr≤0.05%, Zn:≤0.10%, Ti: ≤0.025%, The remainder is Al and unavoidable impurities of up to 0.05 wt. % individually and up to 0.15 wt. % in total, and - recrystallization annealing of the cold rolled strip is carried out at a furnace air temperature of 450°C to 550°C for at least 5 h, and - Intermediate annealing after doubling of the strip is carried out at an air temperature in the furnace of 240°C to 320°C for 0.5 h.
19. The method according to claim 18, It is characterized in that The aluminum alloy has at least one of the following alloy composition limitations in weight %: 0.05%≤Si≤0.30%, 0.8%≤Fe≤1.15%, Cu≤0.05%, 0.018%≤Mn≤0.025%, Mg≤0.01%, Cr≤0.02%, Zn≤0.07% and / or 0.005%≤Ti≤0.025%.
20. The method according to claim 16 or 19, It is characterized in that The rolled ingot was homogenized at 420°C to 600°C for at least 7 hours.
21. The method according to claim 16, It is characterized in that The rolled ingot is hot rolled to a hot rolled final thickness of 2 mm to 4 mm in the hot rolling process, and the hot rolled final temperature is between 300° C. and 350° C.
22. The method according to claim 16, It is characterized in that The final annealing is performed at 200°C to 225°C for at least 150h.
23. Use of the aluminum alloy foil according to any one of claims 1 to 15 in a multilayer composite material.
24. Use of the aluminum alloy foil according to any one of claims 1 to 15 in packaging requiring barrier properties of the aluminum foil.
Citation Information
Patent Citations
Method for manufacturing very thin aluminum-iron alloy strips
US20020043310A1
Aluminum alloy material and manufacturing method for dual-zero aluminium foils
CN101798646A
Aluminum alloy material and method for manufacturing double-zero foil by using same
CN102329988A
Aluminum alloy material and method for manufacturing double-zero foil by using same
CN102329989A
Aluminum alloy and method for manufacturing double-zero foil by using same
CN102329990A